Status Gizi Ibu Saat Hamil, Berat Badan Lahir Bayi Dengan Stunting Pada Balita Usia 06-36 Bulan Di Puskesmas Bontoa - Sukmawati Sukmawati; Hendrayati Hendrayati; Chaerunnimah Chaerunnimah; Nurhumaira Nurhumaira (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
Stunting is the condition of people’s nutrition status in the past through relation to the environment and social economic based on Z-score TB/U in <-2 SD. The causes of Stunting are nutrients intake and infection disease. South Sulawesi is in the third position with dangerous category after Papua and Maluku. Prevalance of stunting in south sulawesi about 38,9% ( shortest 15,8% and short 23,1% ) (Balitbangkes, 2013) The objective of the research is knowing the relation between nutrition status of pregrant woman (LILA) and born weight of infant aged 6-36 months with stunting process in Puskesmas Bontoa, Maros. The type of the research is observational design with “cross sectional study” the samples are all infants aged 6-36 months in Puskesmas Bontoa Maros. The sample methods using simple random sampling with Chi Square test. The result of the research describes that there are 95 respondents for category of pregnant women’s nutrition status (LILA), 28,4% for pregnant woman who experienced chronic energy deficiency. There are 14.7% babies born with low weight (BBLR) and 49.5% infants that suffered stunting for category infant’s nutrition status based on TB/U Stunting. statistics test result shows that there are meaningful relation between pregnant woman’s nutrition status (LILA) with stunting of infant (p= 0.01) and born weight in infants with stunting (p=0.02). The suggestion for officers health need to increase PMT supply to pregnant woman to prevent the increasing number of pregnant woman who suffered chronic energy deficiency in Puskesmas Bontoa Maros